L’ opération typologique: réforme politique et perceptions de la modernité chez les mandarins chinois au tournant du XXe siècle = The typological operation : political reform and perceptions of modernity among Mandarin Chinese people at the turn of the twentieth century - Blitstein, Pablo A. (Politix, 2018)
Today, there are two different understandings of the term "modernity" and its variants. The first understanding is based on a conception that we could call "historical"; it is synonymous with "everything that is happening today." The second understanding is based on a concept that we could call "typological"; in this case, "modernity"-the object of a typological operation-designates a set of characteristic features ("ideal-types") that cannot be found in all societies even when these societies coexist. This article deals with this "typological operation." Through a study of Chinese scholar-officials at the end of the nineteenth and the beginning of the twentieth century, and in particular, of what may be considered one of the Chinese networks of the "nebuleuse reformatrice" [reformative nebula] of the Belle Epoque, this study will describe the emergence of this typological operation in the Chinese-speaking world. We will focus on a paradigmatic case: the reform of educational institutions and the recruitment of civil servants between 1898 and 1911-the last decade of empire in China. Our aim is to describe the relationship between competing reform projects and the perceptions of "modernity" that these projects convey. We will show that these projects not only oppose "typological" and "historical" conceptions of modernity, but also "meritocratic" and "egalitarian" ideals. Secondly, we will examine more closely the trajectory of one of the key actors of these reforms, Kang Youwei (1858-1927), who was also one of the major figures of Chinese nationalism. We will see how, in his projects of reform of the imperial monarchy, he carried out a "typification" of modernity, placing it in opposition with the historical concepts of modernity of some of his adversaries. Finally, we will attempt to understand the "traditional" dimensions that make such a typological operation possible. More precisely, we will explore how some reform-minded Chinese nationalists tried to hold together "modern" and "premodern" intellectual models-in particular linear and cyclical conceptions-and how "typological operations" were actually prefigured by ancient ways of describing historical time.
Gesehen am 03.07.2019